Comprehensive study of Ejecta-companion interaction for core-collapse supernovae in massive binaries - Hirai, R; Podsiadlowski, P; Yamada, S (American Astronomical Society, 2018)
We carry out a comprehensive study of supernova ejecta-companion interaction in massive binary systems. Our aim is to physically understand the kinematics of the interaction and predict observational signatures. To do this, we perform simulations over a vast parameter space of binary configurations, varying the masses of the progenitor and companion, structure of the companion, explosion energy, and orbital separation. Our results were not so consistent with the classical models developed by Wheeler et al. (1975), sometimes deviating by an order of magnitude. Therefore, we construct an alternative simple model that explains the simulated results reasonably well and that can be used to estimate impact velocities for arbitrary explosion profiles and companion star structures. We then investigate the long term evolution after the supernova, where the companion can be inflated by the energy injected into the star. We find that the companion can become more than an order of magnitude overluminous immediately after the supernova but quickly fades away after ~10 years and returns to its original luminosity in about a thermal timescale of the star. Finally, we also discuss the possible surface contamination of heavy elements from the slower ejecta.